The Role of Real-Time Contrast-Enhanced Ultrasound in Guiding Radiofrequency Ablation of Reninoma: Case Report and Literature Review - Zhang, Rui; Xu, Ming; Xie, Xiao-yan (Frontiers in Oncology, 2021)
Background: Reninoma is a rare renal endocrine tumor that can cause secondary hypertension, characterized by hypertension, hypokalemia, high renin and aldosterone with normal aldosterone renin ratio (ARR), and occurs more in young female. Mainstream treatment option is surgery, but is less suitable for small or deep lesions, which makes ablation a promising alternative. Case presentation: Two young female with typical manifestations of reninoma, including hypertension, hypokalemia, high renin, high aldosterone and normal ARR, were treated successfully with real-time contrast-enhanced ultrasound guided radiofrequency ablation, and contrast-enhanced ultrasound was also performed before and after treatment for diagnosis and postoperative assessment. Afterwards, their blood pressure and laboratory tests became normal and remained steady during the follow-up of 32 and 6 months, respectively. Conclusion: Contrast-enhanced ultrasound guided radiofrequency ablations is a promising alternative for reninoma treatment with comparable safety and efficacy with surgery, and has advantages especially in small or deep lesions.